Mavali Concept During Caliphate Period (In the 7-9th Centuries) - Dadayev, Bilal; Balayev, Xaqan; Ocaqlı, Qafar (Scholarya Demo Journal of Ruby, 2020)
Azerbaijan was part of the Arab Caliphate during the 7-9th centuries, hence, the socio-political processes occuring in the Caliphate did not bypass our homeland. Unfortunately, like many other terms evolved in that period, the term “mawali” was not fully mentioned in historical sources and our high school textbooks. The local population who converted to Islam and enlisted in the army in Azerbaijan during the Caliphate for many years, mistakenly pronounced the term as “mövlalar”, “mövliya”, “məvla” and “movla” instead of “mavali”. Consequently, the word “mövlalar” found in Ziya Bunyadov’s works is a plural form of the word “mövla” in the Arabic language used with the suffix “lar” in our language. In this regard, the word mawla can be accepted as a literal translation of the word mawali. The truth is that the word “məvali” is a whole word used separately as the plural form of “mövla” which has an Arabic meaning. In Arabic, “mövla” is not used in plural since it is one of the names of God and is considered inappropriate to name the local people who converted to Islam. The sources we have studied on the subject claim that the concept of mawali had different meanings in different periods due to its diversity, and as a result it was a name given to the population who voluntarily converted to Islam. Gradually Mawalis enlisted in the Arab army, took part in many jihad wars as part of the Caliphate’s army and spread to large areas of the Caliphate. Some of the Mawalis achieved great success in science and art. From the historical sources it is known that many well-known Azerbaijani scientists and cultural figures emerged from the Mawalis during this period.